Molecular Dynamics Study of Vapor-Liquid Equilibrium State of an Argon Nanodroplet and Its Vapor - Hisao YAGUCHI; Takeru YANO; Shigeo FUJIKAWA (Journal of Fluid Science and Technology, 2010)
Molecular dynamics (MD) study of equilibrium system of a single argon nanodroplet and its surrounding argon vapor is carried out to address a fundamental issue whether the thermodynamic description is applicable to the nanoscale inhomogeneous system. The numerical result is sufficiently reliable so that it can identify the smallest droplet standing stably over 200 ns. The validity of the Laplace equation for nanodroplet is proved by a purely mechanical argument on the basis of directly computed normal and tangential pressures in the transition layer. Furthermore, it is demonstrated that the chemical potentials of liquid and vapor phases are not equal when a droplet is so small that the number of molecules consisting the transition layer may be comparable to that in the droplet. The Kelvin equation does not hold in such a case.